COVID-19: HOW DOES IT IMPACT TO THE INDONESIAN ECONOMY? - Astuti, Prihartini Budi; Mahardhika, Arya Samudra (Jurnal Inovasi Ekonomi, 2020)
The Coronavirus began to enter Indonesia in officially in early March  2020. The massive spread of COVID-19 caused a decline in economic activity, and the pandemic has been infected in various sectors such as household consumption, investment, and financial institutions in Indonesia.  There is a threat of loss of community income because they cannot work to fulfill their daily needs, especially for poor and vulnerable households and the informal sector. The decline also occurred at MSMEs. This business actor cannot conduct his business activities so that his ability to fulfill credit obligations is impaired. The corporate sector has also been disrupted, especially in manufacturing, trade, and transportation. The disruption will reduce business performance so that it causes the termination of employment and even bankruptcy. Financial institutions also have the potential to experience liquidity problems, causing depreciation of Indonesian currency, volatility in financial markets, and capital flight.